Modelling of the anti-collision algorithm in RFID system / Shafinaz Ismail - Ismail, Shafinaz (2014)
Radio Frequency Identification (RFID) is a wireless technology that has replaced barcodes. This technology is used in today's world to identify, track, and manage the tagged animate or inanimate objects automatically using wireless communication technology,. Unlike barcode readers, an RFID reader is capable of reading multiple tags located in its range. When this occurs, the probability of tag collision at the reader's end is high. In RFID system, the greatest challenge faced is the tag could not be read due to collisions. To avoid these collisions, there are several anti-collision algorithms used in the RFID system. The major classifications of the algorithms are Aloha based protocols and tree based protocols. This proposal studies on the modeling of the anti-collision algorithm in RFID system and will focus on analyzing the performance of the pure Aloha and slotted Aloha algorithms by deriving the performance metrics of throughput. Theoretical throughput analysis of pure Aloha and slotted Aloha was done and carried out by using Matlab software. Theoretical result was compared with simulation result by Opnet software. The result obtained from the slotted Aloha protocol has shown a better throughput.